Free Allophonic Variation in Native and Second Language Spoken Word Recognition: The Case of the German Rhotic - Llompart, Miquel; Eger, Nikola Anna; Reinisch, Eva (Frontiers in Psychology, 2021)
The question of how listeners deal with different phonetic variant forms for the same words in perception has sparked great interest over the past few decades, especially with regard to lenited and regional forms. However, the perception of free variant forms of allophones within the same syllable position remain surprisingly understudied. Because of this, in the present study, we investigate how free allophonic variation in the realization of the German rhotic (/r/) impacts spoken word recognition for native German listeners and two groups of non-native listeners (French and Italian learners of German). By means of a visual-world eye-tracking task, we tested the recognition of spoken German words starting with /r/ when the rhotic was produced either as the more canonical variant, the uvular fricative [ʁ] which is considered the German standard, or as an alveolar trill [r], a common realization in the south of Germany. Results showed that German listeners were more efficient at recognizing /r/-initial words when these were produced with the uvular fricative than with the alveolar trill. French listeners did not differ from German listeners in that respect, but Italian listeners showed exactly the opposite pattern: they showed an advantage when words were produced with the alveolar trill. These findings suggest that, for native listeners, the canonicity of the variant form is an important determiner of ease of recognition, even in the absence of orthographic or perceptual motivations for the primacy of canonical variants for this particular example of variation. For non-native listeners, by contrast, results are better explained by the match of the different allophones to the canonical realization of /r/ in their native language than by the status or frequency of the allophones in the non-native language itself.